Efficient regulatory approval of two novel HIV prevention interventions in a resource-limited setting: experiences from Zimbabwe - Murombedzi, Caroline; Chirinda, Libert; Chareka, Gift T.; Chirenje, Z. Mike; Mgodi, Nyaradzo M. (Frontiers in Reproductive Health, 2023)
The global burden of HIV remains unacceptably high despite significant progress made in HIV treatment and prevention. There is an urgent need to scale up the comprehensive HIV prevention strategies that include pre-exposure prophylaxis (PrEP). Oral PrEP is highly effective in preventing HIV acquisition when taken regularly, but this remains a challenge for some at-risk individuals. Therefore, there is a need for other HIV prevention options. The dapivirine vaginal ring (DVR) and long-acting injectable cabotegravir (CAB-LA) are novel biomedical interventions that are safe and efficacious for HIV pre-exposure prophylaxis, as demonstrated in recently completed clinical trials. Timely roll-out and scalability of efficacious interventions depend on the registration process with the national medicine regulatory authorities (NMRAs). The Medicines Control Authority of Zimbabwe (MCAZ) was the first NMRA globally to approve the DVR in July 2021 and the first in Africa to approve CAB-LA for HIV prevention in July 2022. The regulatory review process for DVR and CAB-LA by MCAZ took 4.5 and 5.5 months, respectively. This efficient review process of the two interventions by MCAZ, a regulatory body in a resource-limited setting, provides important lessons to shorten timelines between the completion of the clinical development process and the registration of essential medicines.